Selenofuranoside Ameliorates Memory Loss in Alzheimer-Like Sporadic Dementia: AChE Activity, Oxidative Stress, and Inflammation Involvement - Chiapinotto Spiazzi, Cristiano (Oxid Med Cell Longev, 2015)
Alzheimer's disease (AD) is becoming more common due to the increase in life expectancy. This study evaluated the effect of selenofuranoside (Se) in an Alzheimer-like sporadic dementia animal model. Male mice were divided into 4 groups: control, Aβ, Se, and Aβ + Se. Single administration of Aβ peptide (fragments 25–35; 3 nmol/3 μL) or distilled water was administered via intracerebroventricular (i.c.v.) injection. Selenofuranoside (5 mg/kg) or vehicle (canola oil) was administered orally 30 min before Aβ and for 7 subsequent days. Memory was tested through the Morris water maze (MWM) and step-down passive-avoidance (SDPA) tests. Antioxidant defenses along with reactive species (RS) were assessed. Inflammatory cytokines levels and AChE activity were measured. SOD activity was inhibited in the Aβ group whereas RS were increased. AChE activity, GSH, and IL-6 levels were increased in the Aβ group. These changes were reflected in impaired cognition and memory loss, observed in both behavioral tests. Se compound was able to protect against memory loss in mice in both behavioral tests. SOD and AChE activities as well as RS and IL-6 levels were also protected by Se administration. Therefore, Se is promising for further studies.